Improving Learning Outcomes and Student Motivation Through Quizizz Mobile: Peningkatan Hasil Belajar dan Motivasi Siswa Melalui Quizizz Mobile - Jamilah, Jamjam; Suherman, Uman; Kusumaryono, Suyato (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The integration of mobile-based gamification tools in elementary education has emerged as a significant trend to enhance learning engagement and outcomes. Specific Background: Quizizz Mobile, as a gamified learning platform, offers interactive features such as real-time feedback and adjustable quiz settings that align with student-centered learning. Knowledge Gap: Despite the growing use of digital quizzes, limited empirical evidence exists on the effectiveness of Quizizz Mobile specifically in the context of IPAS (Science and Social Studies) education at the Indonesian elementary level. Aims: This study aims to evaluate the effectiveness of Quizizz Mobile in improving students’ motivation and cognitive learning outcomes compared to conventional teaching methods. Results: A quasi-experimental design with pre- and post-tests showed a statistically significant increase in learning outcomes (∆ = 17.86) and motivation in the experimental group using Quizizz Mobile, as opposed to minimal gains in the control group. Novelty: The study highlights the unique combination of mobile-first design and gamification in supporting the Merdeka Curriculum, providing scalable data analytics and learner autonomy. Implications: The findings support the integration of mobile gamified tools in primary education, offering practical insights for educators to enhance motivation and achievement through adaptive, engaging digital learning environments.Highlight : Quizizz Mobile significantly improved students' learning outcomes compared to traditional methods. Gamification features (competition, instant feedback) boosted students' intrinsic motivation. The study supports integrating mobile-based platforms into elementary school IPAS curriculum. Keywords : Quizizz Mobile, Learning Motivation, IPAS, Gamification, Elementary Education